2021
DOI: 10.21203/rs.3.rs-476484/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simple Recycling of Biowaste Eggshells to Various Calcium Phosphates for Specific Industries

Abstract: Egg consumption is very high throughout the world and with it comes enormous amount of waste eggshells. To reduce and utilize these wastes, eggshell wastes were simply transformed to low- or high-purity calcium carbonate grades by washing, crushing, and drying to use as raw materials for producing highly valuable calcium phosphate products. Low-purity calcium carbonate grade was used to prepare triple superphosphate for using in fertilizer industry, whereas high-purity calcium carbonate grade was used to produ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Micropropagation of Anubias sp. 'Petite' research showed that using combination treatment with 75 mg/L Ads and 1-2 mg/L BAP induced 4.93 and 5.03 shoots/explant, respectively (Laohavisuti et al, 2019). Moreover, Laohavisuti et al (2017) used Ads 0, 25, 50 and 75 mg/L combined with BAP 0, 0.5, 1.0 and 1.5 mg/L in micropropagation of the aquatic plant Bucephalandra sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micropropagation of Anubias sp. 'Petite' research showed that using combination treatment with 75 mg/L Ads and 1-2 mg/L BAP induced 4.93 and 5.03 shoots/explant, respectively (Laohavisuti et al, 2019). Moreover, Laohavisuti et al (2017) used Ads 0, 25, 50 and 75 mg/L combined with BAP 0, 0.5, 1.0 and 1.5 mg/L in micropropagation of the aquatic plant Bucephalandra sp.…”
Section: Discussionmentioning
confidence: 99%
“…Several species of the genus Anubias have been propagated via in vitro cultures, such as Anubias congensis (Klomkamhaeng et al, 2021), Anubias sp. 'Petite' (Laohavisuti et al, 2019), Anubias heterophylla (Rittirat et al, 2021) and Anubias barteri var. nana (Rittirat et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the bending stretching mode of the C−O bond symmetrically within calcareous compounds has been identified to exhibit both out-of-plane as well as in-plane vibrations at 872 and 711 cm −1 , respectively; 943 cm −1 is the distinctive band of Si−O bond. 8,10,32,33,38,39 All of the aforementioned compounds were prettily identified with XRF and XRD analysis. Moreover, the impregnation effects of the catalyst are observed around 2323 cm −1 enabling the evolution of a new, substantial O−H binding that remained stable through the conditions of calcination because of the strong chemical attachment properties on the RC-ITB catalyst, while elimination could be possible on the RC one due to the physisorbed nature.…”
Section: Wco's Saponification Number and Free Fatty Acidmentioning
confidence: 99%